Future Directions in Strategic Brand Management Research Using Bibliometric Analysis: A Decade Review - Indriarti, Resti; Hurriyati, Ratih; Dirgantari, Puspo Dewi; Harisandi, Prasetyo (PT. Riset Press International, 2024)
This research aim is to examine future directions in strategic brand management research through a bibliometric computational mapping analysis using VOS viewer. Publish or Perish reference manager application is used to retrieve the Google Scholar database in order to fulfill research data. The title and abstract of the article are used to provide guidance on the search process based on the keywords